Central serous chorioretinopathy: Towards an evidence-based treatment guideline. (November 2019) - van Rijssen, Thomas J.; van Dijk, Elon H.C.; Yzer, Suzanne; Ohno-Matsui, Kyoko; Keunen, Jan E.E.; Schlingemann, Reinier O.; Sivaprasad, Sobha; Querques, Giuseppe; Downes, Susan M.; Fauser, Sascha; Hoyng, Carel B.; Piccolino, Felice Cardillo; et al.
Abstract: Central serous chorioretinopathy (CSC) is a common cause of central vision loss, primarily affecting men 20–60 years of age. To date, no consensus has been reached regarding the classification of CSC, and a wide variety of interventions have been proposed, reflecting the controversy associated with treating this disease. The recent publication of appropriately powered randomised controlled trials such as the PLACE trial, as well as large retrospective, non-randomised treatment studies regarding the treatment of CSC suggest the feasibility of a more evidence-based approach when considering treatment options. The aim of this review is to provide a comprehensive overview of the current rationale and evidence with respect to the variety of interventions available for treating CSC, including pharmacology, laser treatment, and photodynamic therapy. In addition, we describe the complexity of CSC, the challenges associated with treating CSC, and currently ongoing studies. Many treatment strategies such as photodynamic therapy using verteporfin, oral mineralocorticoid antagonists, and micropulse laser treatment have been reported as being effective. Currently, however, the available evidence suggests that half-dose (or half-fluence) photodynamic therapy should be the treatment of choice in chronic CSC, whereas observation may be the preferred approach in acute CSC. Nevertheless, exceptions can be considered based upon patient-specific characteristics. Highlights: The treatment of central serous chorioretinopathy (CSC) is controversial. In chronic CSC, the most effective treatment appears to be half-dose (or half-fluence) photodynamic therapy (PDT). In acute CSC, observation or early half-dose (or half-fluence) PDT can be considered. Future studies will shed light on the efficacy of new treatment strategies.